Study on 100 cases of coronary artery disease underwent percutaneous coronary interventions - BanglaJOL, Administrator; Faruque, Md; Rahman, Fazlur; Reza, AQM; Rahman, Mizanur; Rahman, Sufia; Zaher, Abduz; Hoque, Md Harisul (University Heart Journal, 2009)
This prospective study was done in National Institute of Cardiovascular Diseases, Dhaka, Bangladesh during the period of January 2004 to January2005 to see the effectiveness and safety profile of percutaneous coronary interventions in patients with coronary artery disease. 100 patients with male 90 percent and female 10 percent undergo percutaneous coronary intervention in our unit during this period. Indication of percutaneous coronary interventions were chronic stable angina with stress test positive in 20 percent cases, unstable angina with prior myocardial infarction in 30 percent cases, unstable angina without prior myocardial infarction in 20percent cases, acute inferior myocardial infarction with post myocardial infarction angina in 20 percent cases and acute anterior myocardial infarction with post myocardial infarction angina in 10 percent cases. Angiographic diagnosis of the patients were single vessel disease in 70 percent cases , double vessel disease in 24 percent cases and triple vessel disease in 11 percent cases. Total number of disease coronary arteries was 146 and 125 lesions were treated. Out of 125, 120 lesions were treated with percuteneous transluminal coronary angioplasty with stenting and 5 lesions with plain percuteneous transluminal coronary angioplasty .Total occlusion was treated in 7 cases. Mean diameter of stent used was 3.02 ± 0.42 mm. Patients were discharged by three to four days of the procedure with improved clinical conditions. Residual stenosis after deploying of stent was less than l 0 percent. Our angiographic success rate was 98 percent, procedural success 96 percent and clinical success 95 percent. Failed percuteneous transluminal coronary angioplasty in 2 cases all of them were chronic total occlusion. One patient died on third day of the procedure due to ventricular asystole, he was a patient of triple vessel disease. Following procedure, course of the patients were uneventful. In the field of maagement of coronary artery disease percutaneous coronary intervention is the internationally recognized standard treatment worldwide for more than last 2 decades. From our result it is found that in most of the indicated cases of PCI can be done efficiently with very minimum rate of failure & complication. Key word: Percutaneous coronary interventions, coronary artery disease. doi: 10.3329/uhj.v5i1.3434 University Heart Journal Vol. 5, No. 1, January 2009 13-16